Education And Rapid Response To Choking In Adults: Enhancing Community Awareness And Skills - Hana Priscilla Frudence Sohilait; Tri Wahyuni Ismoyowati (Jurnal Medika: Medika, 2025)
Choking is a medical emergency caused by an obstruction of the airway due to food, liquids, or foreign objects, which can lead to serious complications such as hypoxia, brain damage, and even death. Elderly particularly those with swallowing disorders resulting from degenerative diseases, are at high risk of choking. The objective of this choking management training program is to raise awareness, provide education, and equip the community with first aid skills to reduce the risk of injury and death caused by choking. The benefits include increased public knowledge, improved preparedness among healthcare workers, and the strengthened role of educational institutions in first aid training. The implementation methods included analysis, interactive health education, choking response training, mentoring, and pre- and post-intervention evaluations. The results showed a significant increase in participants’ knowledge and skills in managing choking incidents in adults. This intervention proved to be effective in a community setting and is considered replicable as a strategy to improve community capabilities in handling choking emergencies. The community service outcomes revealed that before the intervention, 43.3% of participants had only moderate knowledge of choking management, and some had poor understanding. After the intervention, there was a marked improvement, with 66.7% of participants demonstrating good skills, and none remaining in the poor category. This intervention is recommended for integration into Puskesmas (community health center) and elderly Posyandu (integrated health posts) programs.